Soil C:N:P stoichiometry and its influencing factors in forest ecosystems in southern China - Lu, Mengzhen; Zeng, Fuping; Lv, Siwei; Zhang, Hao; Zeng, Zhaoxia; Peng, Wanxia; Song, Tongqing; Wang, Kelin; Du, Hu (Frontiers in Forests and Global Change, 2023)
Soil carbon and nutrient contents and their stoichiometric characteristics play a vital role in indicating plant growth and element balance, which can be used to indicate nutrient limitation. However, it has been less studied about their driving factors within forest soils at the regional scale in southern China. In this study, soil organic carbon (SOC), total nitrogen (TN), and total phosphorus (TP) were analyzed in the topsoil (0–10 cm) at 345 sampling plots representing different forest types in Guangxi Province. The results showed that the mean contents of C, N, and P were 29.80, 2.46, and 0.51 g/kg, respectively, and soil C:N, C:P, and N:P were 13.95, 69.60, and 5.53 respectively. The ratios also showed remarkable correlations with each other. C, N, and P contents and their ratios presented significant differences among different soil and vegetation types. C, N, and P concentrations increased with the increase of elevation and latitude, and decrease with the increase of average annual temperature (MAT). Conversely, C:N showed an opposite trend. C, N, and N:P were also increased with increasing average annual precipitation (MAP). Collectively, soil type, vegetation type, geographical, and climatic factors explained 43.46, 64.02, 68.61, 32.93, 39.64, and 37.87% of the variance in C, N, P, C:N, C:P, and N:P, respectively. For Soil C, both latitude and MAP had strong influences. Soil type was the largest explanation for soil N and P contents. Latitude and longitude were the key factors determining the soil stoichiometric ratios. Overall, soil type, geographical and climatic factors were the most vital explanation variables for soil nutrients and their stoichiometric ratios. These results could help improve our understanding of soil stoichiometry within forest ecosystems in southern China.